Answer:
58.1 cm
Step-by-step explanation:
The length of each support rod can be found using the Pythagorean theorem. The geometry can be modeled by a right triangle, such that the distance from centre is one leg and half the length of the rod is the other leg of a triangle with hypotenuse equal to the radius of the grill.
__
<h3>Pythagorean theorem</h3>
The theorem tells us that the sum of the squares of the legs of a right triangle is the square of the hypotenuse. For legs a, b and hypotenuse c, this is ...
c² = a² +b²
<h3>application</h3>
For the geometry of the grill, we can define a=7.5 and c=30. Then b will be half the length of the support rod.
30² = 7.5 +b²
b² = 900 -56.25 = 843.75
b = √843.75 ≈ 29.0473
The length of each support rod is twice this value, so ...
rod length = 2b = 2(29.0473) = 58.0947
Each support rod is about 58.1 cm long.
Answer:
its 11/6
Step-by-step explanation:
GCD of 11 and 6 is 1
Divide both the numerator and denominator by the GCD
11 ÷ 1
6 ÷ 1
Reduced fraction:
11/6
Step-by-step explanation:
high: 91, 91, 91, 91, 90, 90, 92, 94
low:59, 60, 60, 60, 60, 60, 60, 61
Answer:
puedes resolver de dos maneras si diste teorema de Pitágoras lo aplicas
hipotenusa al cuadrado = cateto 2 +cateto 2 ( el 2 significa al cuadrado)
sustituyes
hipotenusa= 4m
cateto= 2,5
hay que hallar el otro cateto que nos daría la altura a la que está la escalera
despejamos y tenemos
cateto 2= hip2 -cat2
cat2=(4)2-(2,5)2=
= 16-6,25=9,75
luego hallamos la raíz cuadrada de 9,75= 3,12
la altura a la que se encuentra es 3,12m
-si aun no diste Pitágoras podes representarlo en una hoja utilizando cm en lugar de metros( a escala). trazas el triángulo rectángulo la base te la da la distancia a la cual se encuentra la escalera de la pared es decir 2,5cm trazas la hipotenusa de 4cm de manera que coincida con el cateto opuesto , y mides el valor de este ,será de 3,12cm no olvides que la respuesta la debes dar en metros ya que es la unidad de medida que te da.
Answer:
Step-by-step explanation:
n = 3 => f(n) = -4*-3+8 = -44
n= 0 => f(n) = -4*0+8 = 8
n= 2 => f(n) = -4*2+8 = 0
n= 7 => f(n) = -4*7+8 = -20